Knowledge and attitude regarding menstrual disorders among undergraduate students at School of Health Sciences, Universiti Sains Malaysia - Rusman, Rabiatul Athirah (2020)
Menstrual disorders are very common among young adults like undergraduate students. Lack of awareness towards the symptoms and early treatment can lead to another gynaecology diseases. It seems that the female undergraduate students used to experience this disorder however it is unsure that their knowledge and attitude towards the symptoms that they experienced were good or poor. Thus, this study aimed to assess the knowledge and attitude level regarding menstrual disorders among undergraduate students at School of Health Sciences, USM Health Campus. Total of 231 undergraduate students, aged between 18 to 29 years old from the eight programmes (Audiology and Speech Pathology, Biomedicine, Dietetic and Nutrition, Environmental and Occupational Health, Forensic Science, Sport Science, Medical Radiation, Degree Nursing and Diploma Nursing) involved in this study. A cross-sectional study design was employed. Data was collected through a set of questionnaires adapted from Nor Asyikin et al. (2016) and analysed using SPSS version 24. Pearson Chi-Square Test was used to identify the association between socio-demographic characteristics with knowledge and attitude level. The majority of the respondents in this study had good knowledge level regarding menstrual disorders (n=202, 87.4%). Among the four factors, only Program of Study was found significant association with knowledge level regarding menstrual disorders (p= 0.002). On the other hand, most of the undergraduate students had poor attitude level regarding menstrual disorders (n= 158, 68.4%). Among the four factors also, only Program of Study was found significant association with attitude level regarding attitude (p = 0.001). These findings revealed that there was a need to increase university students’ awareness and improve their knowledge and attitude level regarding menstrual disorders among undergraduate students as a preventive measure for further gynaecology problems.